2010
DOI: 10.1007/s12011-010-8703-4
|View full text |Cite
|
Sign up to set email alerts
|

Deterioration of Bone Quality by Streptozotocin (STZ)-Induced Type 2 Diabetes Mellitus in Rats

Abstract: Patients with diabetes mellitus (DM) have various skeletal disorders and bone quality can be impaired in DM leading to fractures. Wistar albino male rats (270-300 g; n = 16) were assigned randomly to nondiabetic and diabetic rats (single dose intravenous injection of 45 mg/kg streptozotocin). All rats in each group were perpetuated for 8 weeks, and blood glucose levels as well as body weights were measured once weekly. Biomechanical measurements were performed at the mid-diaphysis of the left femur with tensil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
17
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 43 publications
5
17
0
3
Order By: Relevance
“…Our results showed that BMD of the femur significantly decreased in the STZ rats, which is in agreement with a previous study [29].However, there were also some studies [30,31] that has reported no significant decrease in BMD in STZ-induced diabetic rats. We deduce that the short duration of experiment (8 weeks) in these studies may not be sufficient for the development of bone complications.…”
Section: Discussionsupporting
confidence: 93%
“…Our results showed that BMD of the femur significantly decreased in the STZ rats, which is in agreement with a previous study [29].However, there were also some studies [30,31] that has reported no significant decrease in BMD in STZ-induced diabetic rats. We deduce that the short duration of experiment (8 weeks) in these studies may not be sufficient for the development of bone complications.…”
Section: Discussionsupporting
confidence: 93%
“…Streptozotocin is used to induce both type I and Type II diabetes based on the dose i.e. it is concentration dependent, for the induction of type I, 60 mg/kg is given intraperitoneally or intravenously , and for type II induction 40-50mg/kg is the usual dose used 1,7,8 . In this study the rats were given an intraperitoneal injection of streptozotocin (50 mg kg−1) freshly prepared in 0.1M sodium citrate buffer.…”
Section: Induction Of Diabetesmentioning
confidence: 99%
“…This is exhibited by bone loss in trabecular bone and failure to accrue cortical bone due to premature cessation of growth [14] . Further biomechanical experimental animal studies have demonstrated either increased stiffness [9,15] or reduced stiffness [16][17][18] . These variances are confusing but may be accounted for due to a number of factors.…”
mentioning
confidence: 99%